In vitro cadmium effects on ECM gene expression in human bronchial epithelial cells. Issue 1 (March 2015) - Baroni, Tiziano; Lilli, Cinzia; Bellucci, Catia; Luca, Giovanni; Mancuso, Francesca; Fallarino, Francesca; Falabella, Giulia; Arato, Iva; Calvitti, Mario; Marinucci, Lorella; Muzi, Giacomo; Dell'Omo, Marco; et al.
Highlights We exposed human BEAS-2B cells in vitro to sub-toxic and toxic concentrations of Cd. Sub-toxic Cd dose increased tenascin, vitronectin, β1 and β5 integrin gene expression. The toxic Cd dose decreased type IV and V collagen, α1, α2 and β3 integrins. Each Cd dose caused a different imbalance in the pattern of TGFβ/TGFβR. Cd-induced lung disease may involve downstream changes in TGFβ/TGFβR signaling.